Video games and the law - Gard, Ron; Townsend Gard, Elizabeth 1967-; Billiris, John; Craig, Karl; Donatiello, Mark; Forcell, Markeecha; Lai, Kelvin; Longan, Mitchell; Stork, Alexandra (New York Routledge, 2017)
[Provided by publisher] The video game industry is big business, not only in terms of the substantial revenue generated through retail sales of games themselves, but also in terms of the size and value of parallel and secondary markets. Consider any popular video game today, and you most likely are looking at a franchise that includes not only the game itself and all of its variants but also toys, books, movies, and more, with legions of fans that interact with the industry in myriad ways. Surveying the legal landscape of this emergent industry, Ron Gard and Elizabeth Townsend-Gard shed light on the many important topics where law is playing an important role. In examining these issues, Video Games and the Law is both a legal and a cultural look at the development of the video game industry and the role that law has played so far in this industry's ability to thrive and grow.
Introduction -- Copyright and video games -- Legal issues beyond copyright -- The gaming community and fans -- Employment -- Legal issues with esports -- Conclusion : the new normal.
Keywords: Video games -- Law and legislation -- United States